Type, Intensity, and Duration of Exercise as Regulator of Gut Microbiome Profile. Issue 3 (March 2022) - Suryani, Dini; Subhan Alfaqih, Muhammad; Gunadi, Julia Windi; Sylviana, Nova; Goenawan, Hanna; Megantara, Imam; Lesmana, Ronny
Abstract : Abstract: Gut microbiome profile is related to individual health. In metabolic syndrome, there is a change in the gut microbiome profile, indicated by an increase in the ratio of Firmicutes to Bacteroidetes. Many studies have been conducted to determine the effect of exercise on modifying the gut microbiome profile. The effectiveness of exercise is influenced by its type, intensity, and duration. Aerobic training decreases splanchnic blood flow and shortens intestinal transit time. High-intensity exercise improves mitochondrial function and increases the essential bacteria in lactate metabolism and urease production. Meanwhile, exercise duration affects the hypothalamic-pituitary-adrenal axis. All of these mechanisms are related to each other in producing the effect of exercise on the gut microbiome profile.